Kombinasi Transaksi Penjualan (Merk Beras) Menggunakan Algoritma Apriori (Studi Kasus di UD. SRD) - Iwan Ady Prabowo; Wawan Laksito Yuly Saptomo; Nungky Kurnia Candra (STMIK Sinar Nusantara, 2021)
UD. SRD is an individual company that produces and sells rice with various brands. UD. SRD is an individual company that produces and sells rice with various brands. Rice brands sold include C4 Kelapa, C4 Raja, C4 Merak, Nogo Hitam, Nogo Merah, Nogo Hijau, Pandan Wangi, Mentik Wangi and Rojo Lele. In processing sales data is still done manually that is only using notes or receipts, so the data only serves as an archive. In this study, the data amounted to 404 rice sales transactions from January to September 2016. The purpose of this research is the creation of Apriori algorithm system to predict combination of rice brand in sales transaction in UD. SRD so as to help the company know the sales of the most frequently purchased rice brands simultaneously. The result of combination rice brand is getting using Apriori Algorithm which supported minimum 30% and confidence minimum 70%. It appears from thus statements